2017
DOI: 10.1016/j.psyneuen.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Do women tend while men fight or flee? Differential emotive reactions of stressed men and women while viewing newborn infants

Abstract: Infant care often is carried out under stressful circumstances. Little is known about differences in caretaking motivation between men and women under stress. In the present study, stress was induced in 40 participants (21 women, 19 men) by means of the cold pressor stress test, 40 (22 women, 18 men) serving as controls. Participants then rated their urge to care for newborn infants shown on 20 short video clips. The infants in the videos were either crying (N=10) or were showing typical neonatal facial moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(64 reference statements)
2
10
0
Order By: Relevance
“…Thus, in this competitive context, women, more than men, responded consistently with lower aggression to these prototypically cues of powerlessness. Also in line with the interpretation that women were more sensitive to the opponent's cues of sadness, are the studies suggesting that women display more nurturing, affiliative, and communal behaviors, assume more caretaking‐roles (Eagly et al ., ; Probst, Meng‐Hentschel, Golle, Stucki, Akyildiz‐Kunz & Lobmaier, ), and tend to report higher concern and respond more empathically to others in distress (Singer, Seymour, O'Doherty, Stephan, Dolan & Frith, ; Trobst et al ., ). Yet, another possibility is related to the way people tend to perceive aggression, which may affect their own emotional responses after responding with aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this competitive context, women, more than men, responded consistently with lower aggression to these prototypically cues of powerlessness. Also in line with the interpretation that women were more sensitive to the opponent's cues of sadness, are the studies suggesting that women display more nurturing, affiliative, and communal behaviors, assume more caretaking‐roles (Eagly et al ., ; Probst, Meng‐Hentschel, Golle, Stucki, Akyildiz‐Kunz & Lobmaier, ), and tend to report higher concern and respond more empathically to others in distress (Singer, Seymour, O'Doherty, Stephan, Dolan & Frith, ; Trobst et al ., ). Yet, another possibility is related to the way people tend to perceive aggression, which may affect their own emotional responses after responding with aggression.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a final sample of 61 healthy students, who were assigned either to the control condition (n = 30, 20 women, 10 men) or the stress condition (n = 31, 14 women, 17 men). Assuming a medium effect size f 2 = 0.15 (see Probst et al, 2017;Sherman et al, 2017), the sample size necessary to achieve a power of 0.8 and α = 0.05 was N = 55 for both the main effects and two-way interaction effect, calculated by a priori power analysis using the statistical software G-Power (Faul et al, 2007). As a result, the final sample size N = 61 has exceeded the minimum requirement to reach a reasonable conclusion.…”
Section: Participantsmentioning
confidence: 99%
“…The interaction between crying and the sex of the respondent is difficult to predict, given the inconsistency in previous findings. A recent study with infants suggests that crying may increase negative behaviors in men (Probst et al, 2017), while other studies among adults have not found sex differences in response to crying (Hendriks & Vingerhoets, 2006).…”
mentioning
confidence: 97%
“…lower anticipation of negative emotions, more willingness to trust and to forgive the child, and to use inductive behaviors, and lower estimation of recidivism, warmth removal and overreactivity): (a) More in the conditions where the child cried than in the non-crying conditions; (b) more when the child expressed emotions than in the absence of emotions; and (c) more when the child cried and expressed emotions than in all of the other non-crying conditions. Given the typical higher report of affiliative and caring responses towards children in women than men (Probst et al, 2017;Royle et al, 2012), we expected that women would report more willingness to trust and to forgive the child and would estimate lower misbehavior recidivism than men. We also expected women to report more use of inductive behaviors than males, whereas men would anticipate more overreactivity and warmth removal practices than women (Barnett et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation